2007
DOI: 10.15288/jsad.2007.68.905
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extended Drinking Hours in Ontario on Motor-Vehicle Collision and Non-Motor-Vehicle Collision Injuries

Abstract: Objective-On May 1, 1996, Ontario, Canada, amended the Liquor Licence Act to extend the hours of alcohol sales and service in licensed establishments from 1 AM to 2 AM. The purpose of this study was to evaluate the impact of extended drinking hours in Ontario on motor-vehicle collision (MVC) and other injuries admitted to regional trauma units based on Ontario Trauma Registry data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 7 publications
1
16
2
Order By: Relevance
“…Although the risk of alcohol-attributable injury from motor vehicle accidents (MVA) is the most visible connection in the research literature and popular media, a large body of work has shown that alcohol consumption is broadly associated with the risk of both intentional and unintentional injury in cross-sectional (Watt et al, 2005; Vingilis et al, 2007; Goodman et al, 1991; Malmivaara et al, 1993; Ivers et al, 2006), case-crossover (Borges et al, 2006; Vinson et al, 2003), and case-control analyses (Peck et al, 2008; Smith et al, 2001). The most common mode of sustaining an alcohol-attributable injury is from a single occasion of acute alcohol consumption, most commonly leading to intoxication and/or drunkenness and thus impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk of alcohol-attributable injury from motor vehicle accidents (MVA) is the most visible connection in the research literature and popular media, a large body of work has shown that alcohol consumption is broadly associated with the risk of both intentional and unintentional injury in cross-sectional (Watt et al, 2005; Vingilis et al, 2007; Goodman et al, 1991; Malmivaara et al, 1993; Ivers et al, 2006), case-crossover (Borges et al, 2006; Vinson et al, 2003), and case-control analyses (Peck et al, 2008; Smith et al, 2001). The most common mode of sustaining an alcohol-attributable injury is from a single occasion of acute alcohol consumption, most commonly leading to intoxication and/or drunkenness and thus impairment.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, when laws allowing alcohol sales on Sunday were introduced in New Mexico, the number of alcohol-related traffic deaths and crash fatalities increased relative to the pre-allowance period [5]. Although there are some exceptions to this pattern [8], existing data are broadly consistent with the alcohol availability hypothesis that higher alcohol accessibility predicts both greater alcohol consumption and consumption-related harm [9]. One method of examining the influence of alcohol availability on DWI charges is by investigating the business hours of social premises licensed to serve alcohol (e.g., pubs, bars, clubs and restaurants).…”
Section: Introductionmentioning
confidence: 99%
“…Vingilis and colleagues examined the impact of extended drinking hours on casualties and found a complex pattern of outcomes, whereby in Ontario as a whole, no increases were found in alcohol-related, police-reported motor vehicle collision (MVC) driver fatalities (Vingilis et al, 2005) or in MVC injuries based on hospital trauma data, although increases in non-MVC injuries based on hospital trauma data were found for the time period during which the drinking hour was extended (Vingilis et al, 2007). A survey of licensed establishments in Ontario, reported by Vingilis et al (2005), suggested that some licensed establishments did not implement the extended drinking hours.…”
Section: Introductionmentioning
confidence: 99%